2018
DOI: 10.1103/physrevb.98.014415
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic frustration induced supersolid in the S=12 kagome lattice antiferromagnet in a magnetic field

Abstract: We examine instabilities of the plateau phases in the spin-1/2 kagome-lattice antiferromagnet in an applied field by means of degenerate perturbation theory, and find some emergent supersolid phases below the m = 5/9 plateau. The wave functions of the plateau phases in a magnetic field have the particular construction based on the building blocks of resonating hexagons and their surrounding sites. Magnon excitations on each of these blocks suffer from a kinetic frustration effect, namely, they cannot hop easil… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 66 publications
0
8
0
Order By: Relevance
“…The third challenge is given by the magnetization process of the spin-1/2 KHAF. 26,27,[60][61][62][63][64][65][66][67][68] A series of magnetization plateaus at 3/9(= 1/3), 5/9 and 7/9 of the saturation is found, 26,65,66 among which the 1/3-plateau, already found by Hida, 60 is the widest. In addition to the above mentioned plateaus, there might be a tiny plateau at 1/9.…”
Section: Introductionmentioning
confidence: 72%
“…The third challenge is given by the magnetization process of the spin-1/2 KHAF. 26,27,[60][61][62][63][64][65][66][67][68] A series of magnetization plateaus at 3/9(= 1/3), 5/9 and 7/9 of the saturation is found, 26,65,66 among which the 1/3-plateau, already found by Hida, 60 is the widest. In addition to the above mentioned plateaus, there might be a tiny plateau at 1/9.…”
Section: Introductionmentioning
confidence: 72%
“…Accordingly a SS state is defined as a state having both the orders of the solid and the SF phases [35]. The search for SS phases has extensively been performed in recent years [36][37][38][39][40][41][42][43]. For example, the SS phases have been observed in SrCu 2 (BO 3 ) 2 with spin-1/2 Shastry-Sutherland lattice [40,41] and Cr spinel compounds with spin-3/2 pyrochlore lattice [42,43].…”
Section: Introductionmentioning
confidence: 99%
“…Quantum fluctuations will give rise to exotic quantum superposition states of degenerate configurations, which can open up a way to novel quantum spin liquids at the magnetization plateaus. Indeed, various exotic plateaus have been found in quantum kagome magnets, 42,43) and extensive theoretical and numerical studies [44][45][46][47][48][49][50][51][52][53] have revealed that the formations of such plateaus are often attributed to the superstructures of magnons and/or valence bonds. In particular, the authors of Ref.…”
mentioning
confidence: 99%